1988
DOI: 10.1155/1989/28161
|View full text |Cite
|
Sign up to set email alerts
|

A new Simplified Method of Selective Exposure of Hepatic Pedicles for Controlled Hepatectomies

Abstract: Our experience of 90 hepatectomies (HE) and examinations of 64 cadaver livers resulted in the elaboration of a simplified technique for the exposure of hepatic pedicles (HP) and the rapid selective ligation without significant normothermal ischemia of the retained parts of the liver. The method comprises 4 consecutive steps: 1) a superficial T-shaped incision of Glisson's capsule at the site of HP projection on the liver's inferior surface, 2) introduction of the surgeon's forefinger into the liver parenchyma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 2 publications
0
26
0
4
Order By: Relevance
“…In this method, because the full length of the primary branches and the origin of the secondary branches are located extrahepatically, the origin of the three segmental branches can easily be taped outside the liver without having to incise the liver parenchyma. In 1990, Galperin and Karagiulian [7] used small incisions on the inferior surface of the liver, tunneling into the liver parenchyma until the sheath was found. In fact, it is not easy to tape each secondary branch without any division of the liver parenchyma because the sense of touch is not utilized in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, because the full length of the primary branches and the origin of the secondary branches are located extrahepatically, the origin of the three segmental branches can easily be taped outside the liver without having to incise the liver parenchyma. In 1990, Galperin and Karagiulian [7] used small incisions on the inferior surface of the liver, tunneling into the liver parenchyma until the sheath was found. In fact, it is not easy to tape each secondary branch without any division of the liver parenchyma because the sense of touch is not utilized in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Galperin and Karagiulian11 introduced the technique of selective exposure of the hepatic pedicles and rapid selective ligation without significant normothermal ischemia of the retained parts of the liver. They reported that this selective ligation technique, using the intrahepatic Glissonian approach, could reduce the blood loss and duration of general liver ischemia during hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, Lin et al [5], Ton-That-Tung and Nguyen-Duong-Quang [6] and Okamoto [7] successfully performed the intrahepatic Glissonean pedicle isolation with major liver transection through the main portal fissure. Meanwhile, Galperin and Karagiulian described the intrahepatic approach with minor transection using digitoclasia in 1989 [8] and Machado et al reported the same type of approach using a clamp or a vascular stapler [9,10]. However, the intrahepatic isolation might be accompanied by a potential risk of unexpected injury to the portal pedicle or the hepatic vein.…”
Section: Historical Considerations About the Glissonean Pedicle Isolamentioning
confidence: 99%